SYNERGISTIC EFFECT OF ORAL ALLOPURINOL AND INTRALESIONAL SODIUM STIBOGLUCONATE IN THE TREATMENT OF CUTANEOUS LEISHMANIASIS - Rashid, Haroon ur; Ullah, Ihsan; Adeeb, Humera; Zeb, Mubarak; Mohammad, Amir; Rehman, Naumana (Journal of Ayub Medical College Abbottabad, 2020)
Background: Leishmaniasis is an endemic disease and a major public health problem throughout the world. Its geographic distribution has been extended over the past few years in Pakistan. The available treatment options of Leishmaniasis are limited and mostly parenteral, and hence a non-toxic oral alternative therapy is urgently needed to overcome the problem. The objective of this study was to evaluate the synergistic effect of Allopurinol as an adjunct therapy along with conventional intra-lesional sodium Stibogluconate in the treatment of cutaneous Leishmaniasis. Methods: This single blinded randomized controlled trial was carried out at the tertiary care hospitals of district Peshawar, Pakistan. A total of one hundred and sixty-four (164) patients of age range from 19-56 years, consisting of both genders were included in this study. All subjects were randomly allocated to Group-1 and Group-2 where each group had 82 patients of comparable age and genders. Group-1 patients were given an intra-lesional injection of sodium Stibogluconate at a dose of 1-5 ml depending on the lesion size, where one ml injection contained 100 mg of the drug. Group-2 patients were given combination therapy of oral Allopurinol (20 mg/kg/day in divided doses) along with the same intra-lesional sodium Stibogluconate dose as group-1 until complete cure of the lesion. Results: Combination therapy of sodium Stibogluconate along with Allopurinol was found superior to sodium Stibogluconate alone in terms of duration of treatment. Group-1, patients who received only sodium Stibogluconate required prolonged treatment duration of 6-9 weeks depending upon the lesion size, while group-2 patients who received combination therapy of sodium Stibogluconate and Allopurinol responded more quickly and their lesions cured in 3-6 weeks depending upon the lesion size. Conclusion: Oral Allopurinol has a synergistic effect when used with intra-lesional sodium Stibogluconate and effectively reduces the treatment duration required for complete cure of cutaneous Leishmaniasis. Treatment duration was reduced by 3 weeks in the present study when combination therapy was given to the patients of cutaneous Leishmaniasis. Keywords: Allopurinol; Cutaneous leishmaniasis; Sodium Stibogluconate; Leishmania